In vivo photoacoustic imaging dynamically monitors the structural and functional changes of ischemic stroke at a very early stage - Lv, Jing; Li, Shi; Zhang, Jinde; Duan, Fei; Wu, Zhiyou; Chen, Ronghe; Chen, Maomao; Huang, Shanshan; Ma, Haosong; Nie, Liming (Theranostics, 2020)
Ischemic stroke (IS) is one of the leading causes of death and accounts for 85% of stroke cases. Since the symptoms are not obvious, diagnosis of IS, particularly at an early stage, is a great challenge. Photoacoustic imaging combines high sensitivity of optical imaging and fine resolution of ultrasonography to non-invasively provide structural and functional information of IS. : We adopted three rapid photoacoustic imaging systems with varying characteristics, including a portable handheld photoacoustic system, high-sensitivity bowl-shaped array photoacoustic computed tomography (PACT), and high-resolution photoacoustic microscopy (PAM) to assess the stereoscopic and comprehensive pathophysiological status of IS at an early stage. Two representative models of IS, referring to photothrombosis and middle cerebral artery occlusion (MCAO) models, were established to verify the feasibility of photoacoustic imaging detection. Non-invasive, rapid PACT of the IS model in mouse provided structural information of the brain lesion, achieving early disease identification (5 min after the onset of disease). Moreover, it was able to dynamically reflect disease progression. Quantitative high-resolution PAM allowed observation of pathological changes in the microvascular system of mouse brain. In terms of functional imaging, significant differences in oxygen saturation (sO ) levels between infarcted and normal areas could be observed by PACT, permitting effective functional parameters for the diagnosis of IS. We used PACT to perform full-view structural imaging and functional imaging of sO in IS at the macroscopic level, and then observed the microvascular changes in the infarcted area at the microscopic level by using PAM. This work may provide new tools for the early diagnosis of IS and its subsequent complications as well as assessment of disease progression.